Pengaruh Hasil Belajar Metode Mengajar Khusus terhadap Kesiapan Mahasiswa Teknik Elektro Melaksanakan Praktek Lapangan Kependidikan - Farras, Naufal Bari; Usmeldi, Usmeldi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
This research aims to determine the influence of learning outcomes of special teaching methods on electrical engineering students' readiness to carry out practical field education. This research method uses a quantitative approach, meaning all data or information is based on statistical analysis. The type of research used is associative research. The subjects of this research were students at Padang State University, the Electrical Engineering Education study program, totaling 43 students. The research instrument used a questionnaire and a trial was carried out before the questionnaire was distributed to students. The questionnaire was tested for validity and reliability after a trial. Research data will be measured using a 1-5 Likert scale. In this research, data analysis uses a simple linear regression test. The t-test was also carried out to test the effect of the independent variable on the dependent variable. The research results show that there is an influence of learning outcomes from certain teaching methods on the readiness of electrical engineering students.